Long-Run and Short-Run Determinants of Sovereign Bond Yields in Advanced Economies - Poghosyan, Tigran (IMF Working Papers; Working Paper, 2012)
We analyze determinants of sovereign bond yields in 22 advanced economies over the 1980-2010 period using panel cointegration techniques. The application of cointegration methodology allows distinguishing between long-run (debt-to-GDP ratio, potential growth) and short-run (inflation, short-term interest rates, et cetera) determinants of sovereign borrowing costs. We find that in the long-run, government bond yields increase by about 2 basis points in response to a 1 percentage point increase in government debt-to-GDP ratio and by about 45 basis points in response to a 1 percentage point increase in potential growth rate. In the short-run, sovereign bond yields deviate from the level determined by the long-run fundamentals, but about half of the deviation adjusts in one year. When considering the impact of the global financial crisis on sovereign borrowing costs in euro area countries, the estimations suggest that spreads against Germany in some European periphery countries exceeded the level determined by fundamentals in the aftermath of the crisis, while some North European countries have benefited from 'safe haven' flows.